INTERAKSI EDUKATIF DALAM PEMBELAJARAN METODE YANBUA DI MADRASAH DINIYAH HIDAYATUL MUBTADI-IEN KAYUHAN KULON - Arina Mustafidah (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2021)
Education can be implemented properly if all learning processes and activities have the role of teachers and students, which is called educative interaction. As in Madrasah Diniyah Hidayatul Mubtadi-ien (Madin HM) Kayuhan Kulon, interactions between teachers and students also occur. Even the role of the teacher is very decisive for the quality of student reading, because Madin HM Kayuhan Kulon applies the Yanbu'a method in facilitating the needs of students in reading and writing the Koran. The importance of the interaction relationship also determines the success rate of learning this Yanbu'a method. This study aims to determine the educational interactions contained in Yanbu'a learning. This research uses descriptive qualitative method. The study was taken at Madin HM Kayuhan Kulon, including teachers, the head of Madin, and students, the majority of whom were elementary school age students. Data collection was done by observation, interviews and documentation. Data analysis was carried out by referring to the Milles and Huberman procedures, which included data reduction, data display, and conclusion drawing, respectively. The results showed that the Yanbu'a learning applied at Madin HM Kayuhan Kulon was in accordance with the characteristics of educative interactions. The Yanbu'a method at Madin HM Kayuhan Kulon is in accordance with the characteristics of educative interactions. Namely 1) have a purpose in each material; 2) there is a learning procedure to achieve the goal; 3) the existence of special materials that are already available in the Yanbu'a book; 4) the existence of student activities; 5) the existence of teacher guidance; 6) apply discipline in terms of reading and writing according to Yanbu'a material; 7) there is a limitation of study time; and 8) there is an evaluation from the teacher.